2021
DOI: 10.1021/acs.energyfuels.0c04248
|View full text |Cite
|
Sign up to set email alerts
|

Technical Aspects of the Pore Structure in Shale Measured by Small-Angle and Ultrasmall-Angle Neutron Scattering: A Mini Review

Abstract: Small-angle neutron scattering (SANS) and ultrasmall-angle neutron scattering (USANS) are special and powerful tools to study micro-, meso-, and macropores from 1 nm to 10 μm in size in disordered systems. Neutron scattering measurements are often integrated with fluid-invasion methods to provide a comprehensive understanding of the pore space in shale. The first SANS study of shale samples was dated back to the early 1980s. The interest was renewed around 2011, and the number of studies that applied SANS/USAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 69 publications
(224 reference statements)
0
6
0
Order By: Relevance
“…We describe the porosity evolution of water-containing Al 2 O 3 based on the modelindependent Porod invariant method, which is widely used to determine the total porosity of samples. 25 The porosity could be estimated using the Porod invariant, Q inv , in a two-phase system, as follows 26…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We describe the porosity evolution of water-containing Al 2 O 3 based on the modelindependent Porod invariant method, which is widely used to determine the total porosity of samples. 25 The porosity could be estimated using the Porod invariant, Q inv , in a two-phase system, as follows 26…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Small-angle neutron scattering (SANS) is a powerful tool for studying pore morphologies in porous media containing pores ranging from 1 nm to several hundred nanometers in diameter. Ultra-small-angle neutron scattering (USANS) extends the measurement range up to several microns. Because fluid invasion approaches, such as gas physisorption and mercury intrusion porosimetry, detect only connected pores accessible from the sample surface, integrating SANS with these techniques can yield information regarding both accessible and inaccessible pores of the material based on the total porosity .…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al presents a comprehensive review on the current status, geological challenges, and future directions for shale gas exploration and development in China. The second review by Zhang and Cheng is a mini review on the technical aspects of sample preparation and data analysis using small-angle neutron scattering (SANS) and ultrasmall-angle neutron scattering (USANS) for shale samples. The original research articles cover a wide spectrum of research on shale gas, including reservoir characteristics, ,,, reservoir modeling, ,,, exploration, equipment-related, ,, gas transport properties, ,,,, shale property characterization, , gas adsorption, ,, gas generation, produced water treatment, , methane conversion, etc.…”
Section: Shale Gasmentioning
confidence: 99%
“…Many methods have been applied in characterizing nanopores in coal and shale, including X‐ray fluorescence spectroscopy (XRF) (Dong & Tan, 2010), optical microscopy, scanning electron microscopy (SEM) (Garum et al, 2020), micronano computed tomography (micronano CT) (Han et al, 2015; Zhao et al, 2019), focused‐ion beam‐scanning electron microscopy (FIB‐SEM) (Wang et al, 2018; Zhu, Huang, et al, 2021), small‐angle X‐ray scattering (SAXS) (Sun et al, 2020), small‐angle neutron scattering (SANS) (Sun et al, 2020; Zhang & Cheng, 2021), mercury porosimetry (Huang et al, 2018; Jiao et al, 2020), nitrogen adsorption (Jia et al, 2020), helium pycnometry (Han et al, 2021), nuclear magnetic resonance (NMR) (Benavides et al, 2020) and transmission electron microscopy (TEM) (Zhu, Huang, et al, 2021), as shown in Figure 1. Determining pore sizes by XRF is based on the relationships between Si and Fe elements and skeleton particles and muddy interstitial materials, which are limited in detecting microscale to nanoscale pores.…”
Section: Introductionmentioning
confidence: 99%